Augmented Space Recursion Method for the Study of Electronic States of Binary Alloys (Bangladesh Journal of Scientific and Industrial Research, 2010)
We have studied here the electronic structure of pure random disordered alloys formed by Ni with Cu and Au at different ratios by using the linearized tight-binding muffin-tin Orbital (TB-LMTO) method. We also used the recursion technique together with augmented space formalism for increasing the efficiency and the accuracy to calculate the component projected density of states. From the density of state, we can understand the Fermi energy, magnetic moment and binding energy at different alloy compositions. The band structure can be calculated from here also. These studies are helpful for experimentalists and metallurgists in designing materials and alloys with specific properties. Key words: Electronic structure, Alloys, TB-LMTO, Density of states, Augmented space recursion   DOI: 10.3329/bjsir.v44i3. Bangladesh J. Sci. Ind. Res. 44(3), 255-264, 2009